Potential Impediments to Long-Term and Low-Carbon Investment: The International Accounting Standards at Stake - Rigot, Sandra; Demaria, Samira (International Journal of Sustainable Energy Planning and Management, 2018)
This paper[i] aim to understand the role of today’s accounting requirements for financial intermediaries (banks and insurers), to be aware of their limitations and to underscore the need for reform in order to foster long-term and then low-carbon capital spending in Europe. The paper shows that International Financial Reporting Standards (IFRS) can affect long-term asset allocation of banks and insurance companies. International accounting standards do not differentiate between low and carbon intensive investment and do not take into account climate risks beforehand. To tackle these issues, we make some recommendations to promote long term and low-carbon investment. [i] This paper was elaborated as part of a partnership with the French Accounting Standards Setter (Autorité des Normes Comptables, ANC), the Foundation for the research of the Caisse des Dépôts (CDC) and BNP Paribas between June 2013 and December 2015.